Studi Penyelenggaraan Pelayanan Kesehatan Lingkungan Di Puskesmas Kota Denpasar Tahun 2020 - Ni Luh Putu Adelia Irmayanti; Anysiah Elly Yulianti (Jurnal Kesehatan Lingkungan (JKL), 2020)
Abstract.For the implementation of environmental health services in the Public health center need to be analyzed human resources, funding sources, implementation activities, and infrastructure facilities. The purpose of this research is to determine the implementation of environmental health services. Research is conducted throughout the public health center of Denpasar City, by providing an overview, description and analysis of the implementation of environmental health services. The results showed human resources showed a 100% good figure, all respondents of 100% expressed the importance of funding sources, as many as 5 public health centers carry out environmental health services every day, and the remaining 6 public health centers carry out according to the schedule. Facilities and infrastructures at the Public health center of Denpasar City there are still less like environmental health laboratories, environmental quality gauges and tool repair tools. Thus it is advised that the public health center that facilities and infrastructure is still lacking to be equipped and to the Public health center that carries out the activities of environmental health services on a schedule/not daily to review to the implementation of environmental health services